2014
DOI: 10.1007/s00417-014-2624-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the exudation recurrence after cataract surgery in patients previously treated with anti-vascular endothelial growth factor for exudative age-related macular degeneration

Abstract: Cataract surgery was beneficial in patients previously treated with anti-VEGF for exudative AMD. Our data suggests that cataract surgery should be performed after a sufficiently long exudation-free period to minimize exudation recurrence. But larger prospective studies are required to draw definitive clinical guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…2 Despite showing an overall improvement in vision following cataract extraction, our study showed worsening of select anatomic parameters on ocular coherence tomography (OCT), such as the presence of cysts and central thickness in eyes following cataract surgery. 1 As Dr Kim noted, our physicians utilized a treat-and-extend (TAE) approach to treating wet agerelated macular degeneration (wet AMD), which indicates that an anti-vascular endothelial growth factor (anti-VEGF) injection was given at each visit even if there was no exudation (defined as hemorrhage, subretinal fluid, or intraretinal cystoid changes).…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…2 Despite showing an overall improvement in vision following cataract extraction, our study showed worsening of select anatomic parameters on ocular coherence tomography (OCT), such as the presence of cysts and central thickness in eyes following cataract surgery. 1 As Dr Kim noted, our physicians utilized a treat-and-extend (TAE) approach to treating wet agerelated macular degeneration (wet AMD), which indicates that an anti-vascular endothelial growth factor (anti-VEGF) injection was given at each visit even if there was no exudation (defined as hemorrhage, subretinal fluid, or intraretinal cystoid changes).…”
contrasting
confidence: 52%
“…1 As Dr Kim noted, our physicians utilized a treat-and-extend (TAE) approach to treating wet agerelated macular degeneration (wet AMD), which indicates that an anti-vascular endothelial growth factor (anti-VEGF) injection was given at each visit even if there was no exudation (defined as hemorrhage, subretinal fluid, or intraretinal cystoid changes). 2 Given that anti-VEGF injections are a relatively low-risk procedure, these findings support the use of a prophylactic injection in PRN protocols, or reducing the treatment interval in TAE protocols in the perioperative period. Our analysis included only the 1-year period around cataract surgery (6 months before and after), and expanding the analysis of the notes and images for all patients was not possible in the time given to respond.…”
mentioning
confidence: 66%
“…Our study is not the first (Jonas et al 2007;Furino et al 2009;Rosenfeld et al 2011;Tabandeh et al 2012;Grixti et al 2014;Lee et al 2014) to evaluate visual outcome and frequency of anti-VEGF injections in patients with neovascular AMD undergoing cataract surgery, but it is the largest and it has the longest follow-up. We found that cataract surgery improved visual acuity by 7.0 ETDRS letters at 6 months after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any changes in the frequency of anti-VEGF injections when comparing data for up to 18 months before and after cataract surgery suggesting that cataract surgery did not influence the course of exudative AMD. A study on 39 eyes of 39 patients who had been treated for neovascular AMD but had been inactive for a mean of 12 months found that the majority of patients gained visual acuity or remained stable after cataract surgery but 7% had lost more than three lines at 6-month follow-up (Lee et al 2014). Our study is not the first (Jonas et al 2007;Furino et al 2009;Rosenfeld et al 2011;Tabandeh et al 2012;Grixti et al 2014;Lee et al 2014) to evaluate visual outcome and frequency of anti-VEGF injections in patients with neovascular AMD undergoing cataract surgery, but it is the largest and it has the longest follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neovascular AMD, can compromise in 90% of cases severely the vision (20/200 or worse) if left untreated [37], but with the advent of anti-vascular Endothelial Growth Factor (anti-VEGF) intravitreal injections as therapy in wet AMD has got stabilize (90%) or even improved vision (30%) in a large number of cases [38][39][40][41][42][43].…”
Section: Neovascular Amdmentioning
confidence: 99%